Koordinasi Antar Lembaga Desa dalam Pembangunan Desa Rato Kecamatan Lambu Kabupaten Bima - Wawan Mulyawan (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
The process of planning, implementing, controlling, and maintaining, as well as developing development results is one of the keys to the success of any development effort. However, coordination is the organization of the relationship of joint efforts to obtain unity of action in achieving goals. Coordination is an effort to adjust different parts, so that the activities of the parts are completed on time, so that each can contribute its maximum efforts, in order to obtain overall results. Coordination of a large number of parts in any organization-wide effort is so important that some put it at the center of analysis. Effective coordination is a necessity to achieve good administration/management and is a direct responsibility of the leadership. Coordination and leadership are inseparable and therefore influence each other. Effective leadership will ensure good coordination because the leader acts as a coordinator